Is ambition a gendered issue? Students´ vs employees´ antecedents of Ambition about Leadership - Lopez-Zafra, Esther; Sánchez-Álvarez, Nicolás; Carmona-Cobo, Isabel (Anales de Psicología / Annals of Psychology, 2021)
Obstacles along women career demonstrate how ambition for becoming a leader is complex because it is influenced by gender stereotypes and roles. In this study, 625 participants (54.24% women) from two statuses (379 students and 246 employees) were asked to imagine how they would react to a promotion to a leadership position and then completed a questionnaire including their beliefs about the consequences, core self-evaluations, ambition, positive and negative emotions, and gender role ideology. Students were more ambitious than employees, regardless of their gender. However, when analyzing the impact of ambition on the decision of accepting a leadership position we observe that positive affect generated by imagining a promotion is the key aspect to finally decide to accept the promotion in both students and employees. However, in students, regardless of their gender, the decision is predicted by negative affect, core-self evaluations but not by levels of ambition.